Newspapers as teaching tools for media literacy education what makes teachers use newspapers in their classrooms?. Issue 4 (1st October 2020) - Simons, Mathea; Smits, Tom F.H.; Janssenswillen, Paul
ABSTRACT: In many countries stakeholders take initiatives to stimulate students' media literacy, such as (free) distribution of newspapers to teachers, the so-called Newspapers in Education (NiE) programmes. The aim of these initiatives is to promote reading, stimulate interactive ways of teaching and create a generation of critical thinkers and informed citizens. The success and effectiveness of initiatives of this kind depend on how teachers use newspapers as teaching tools in class. In this study we examine the use of a local NiE programme and shed light on its determining factors. 454 Flemish teachers (Belgium) in primary and secondary education and 219 student teachers (Bachelors and Masters) participated in the study, which followed a mixed-methods approach. The results show that if newspapers are (freely) distributed, teachers use them as teaching tools quite intensively as teaching tools. One of the most determining factors is the extent to which teachers use media themselves and work on media creation in their classrooms. This finding indicates that school board members, pedagogical counsellors and teacher educators can support and stimulate NiE programmes by paying explicit attention to these elements, e.g., during pre- and in-service training as well as by focusing on the development of media literacy competencies of teachers.